Características significativas de prescripción dietética en el Hospital Nacional Dos de Mayo y Clínica Good Hope, mayo–agosto del 2008 - Cinthia Carel Flores Quinteros (2019)
Purpose. To determine the significant characteristics of dietary prescription at the Dos de Mayo General Hospital,and the Good Hope Private Hospital; may-sugust, 2008. Methodology: The present study was descriptive, crosssectional. The sample units for both study centers were 41 medical histories. In first place an analysis guide wasapplied from the medical histories in both study centers, and then a knowledge survey about medical nutrition wasapplied to the Dos de Mayo General Hospital. The data processing and analysis was performed through the WindowsStatistical SPSS Software. Results: In the obtained results we can observe in regard to the Dietary Prescriptionand its characteristics what such a prescription must have; that at the Dos de Mayo General Hospital 22% take inaccount the characteristics that a Dietary Prescription must have. While at the Good Hope Private Hospital 100%,take in account the characteristics that a Dietary Prescription must have, which is a relevant fact and an exampleto be followed since this is important in order for the patient to recuperate because through the feeding process thepatient can be supplied with nutrients that he needs for his recovery. It is important to stress that this prescriptionmust be done by the nutritionist, for the nutritionist holds the necessary knowledge in order for the prescription tobe effective.